2021
DOI: 10.1002/ped4.12290
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii infection in children after allogeneic hematopoietic stem cell transplantation: A case report and literature review

Abstract: Introduction Toxoplasmosis is a life‐threatening complication after hematopoietic stem cell transplantation (HSCT). However, for several reasons, clinicians know little about Toxoplasma infection. Case presentation We report a case of toxoplasmosis that was diagnosed by bone marrow smear and metagenomic next‐generation sequencing (mNGS) after HSCT in a boy. Additionally, we summarize the characteristics of toxoplasmosis after pediatric HSCT reported in the literature published in PubMed. Conclusion Clinicians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…To date, 4 cases have been reported that have shown that mNGS led to a final diagnosis of T. gondii infection after HSCT as reviewed in Table 1. 22–25 To our knowledge, our study is the first to report T-ALL with primary T. gondii infection, especially in a patient with an atypical continuously seronegative condition after HSCT, further highlighting the promising advantages of mNGS in rapid diagnosis without any other indicative clues. In particular, we aimed to emphasize 2 key points: (1) the importance of early application of mNGS as long as infection is suspected.…”
Section: Discussionmentioning
confidence: 62%
“…To date, 4 cases have been reported that have shown that mNGS led to a final diagnosis of T. gondii infection after HSCT as reviewed in Table 1. 22–25 To our knowledge, our study is the first to report T-ALL with primary T. gondii infection, especially in a patient with an atypical continuously seronegative condition after HSCT, further highlighting the promising advantages of mNGS in rapid diagnosis without any other indicative clues. In particular, we aimed to emphasize 2 key points: (1) the importance of early application of mNGS as long as infection is suspected.…”
Section: Discussionmentioning
confidence: 62%
“…May be a clue to early prediction or diagnosis of HHV-6 encephalitis. 11,12 It has also been suggested that preexisting hyponatremia may also be a potential marker for predicting HHV-6 encephalitis in adults after HSCT. 13 In our study, four patients with HHV-6 encephalitis developed intractable hyponatremia during the course of the disease, and the decrease in serum sodium levels all preceded the onset of encephalitis by 1-2 days.…”
Section: Discussionmentioning
confidence: 99%